2009
DOI: 10.1158/0008-5472.can-08-3845
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia as a Prognostic Factor for Overall Survival in Advanced Carcinomas, Sarcomas, and Lymphomas

Abstract: Lymphopenia is frequent in advanced cancers and predicts the toxicity of chemotherapy. Its effect on relapse and survival is uncertain. Its prognostic value for survival was analyzed in three databases of previously reported prospective multicenter studies: (a) FEC chemotherapy in metastatic breast carcinoma; (b) CYVADIC in advanced soft tissue sarcoma (European Organization for Research and Treatment of Cancer-Soft Tissue and Bone Sarcoma Group 62791); and (c) prospective, consecutive phase III studies of agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
498
4
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 689 publications
(529 citation statements)
references
References 45 publications
22
498
4
5
Order By: Relevance
“…16,17 More generally, T cell lymphopenia has been shown to be a grave prognostic indicator in multiple types of cancers. [18][19][20][21][22][23] Recently, digital PCR platforms have been developed that offer advantages over real time qPCR including the capability to obtain absolute quantification without external references and to be highly robust to variations in PCR efficiency, thus improving assay precision. [25][26][27] Digital PCR is based on limiting dilution of a sample into a large number of separate PCR reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 More generally, T cell lymphopenia has been shown to be a grave prognostic indicator in multiple types of cancers. [18][19][20][21][22][23] Recently, digital PCR platforms have been developed that offer advantages over real time qPCR including the capability to obtain absolute quantification without external references and to be highly robust to variations in PCR efficiency, thus improving assay precision. [25][26][27] Digital PCR is based on limiting dilution of a sample into a large number of separate PCR reactions.…”
Section: Introductionmentioning
confidence: 99%
“…23) In different types of cancer, if a cancer patient has a lower peripheral blood lymphocyte count, he or she has a poorer chance of survival. 24,25) An association between high NLR and worse prognostic outcomes has been well demonstrated in various non-thyroid cancers, including gastric, colorectal, lung, pancreatic, hepatocellular, renal cell carcinoma, cholangiocarcinoma and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, women with an ALC ≥ 2.0 × 10 9 /L at diagnosis had a superior 5-year survival for stage I (80%), stage II (63%), and stage III (53%) compared with breast cancer patients with an ALC < 2.0 × 10 9 /L for stage I (74%), stage II (44%), and stage III (18%) [11]. In a large cohort of 287 hormone-resistant metastatic breast cancer patients, Ray-Coquard et al [8] showed superior overall and progression-free survival for patients with an ALC ≥ 1.0 × 10(9)/L compared with those who did not prior to treatment [median overall survival: 13.6 months versus 9.5 months, P < .0001; and median progressionfree survival: 8.5 months versus 6.8 months, P < .0001, respectively]. In a cohort of 113 women with metastatic or recurrent breast cancer, patients with a higher peripheral blood CD8 count experienced superior survival.…”
Section: Absolute Lymphocyte Count At Diagnosismentioning
confidence: 97%
“…More recently, ALC at diagnosis appears to also predict survival in patients with in diffuse large Bcell lymphoma (DLBCL) improving the prognostic ability of the International Prognostic Index [4][5][6], as well as in follicular lymphoma, augmenting the prognostic ability of the Follicular Lymphoma International Prognostic index (FLIPI) [7]. Using an ALC cut-off values of 1.0 × 10(9)/L, Ray-Coquard et al [8] reported in a large cohort of 322 nonHodgkin's lymphoma (NHL) patients poor clinical outcomes in patients with an ALC < 1.0 × 10(9)/L. The median overall survival was 11.3 months for NHL patients with an ALC < 1.0 × 10(9)/L compared with 94.3 months for NHL patients with an ALC ≥ 1.0 × 10(9)/L.…”
Section: Absolute Lymphocyte Count At Diagnosismentioning
confidence: 99%